(untitled) (World Bulletin of Social Sciences, 2025)
This article provides information on the initiation, goals, and objectives of senatorial investigations conducted throughout the governorates of the Russian Empire, the guidelines developed for these investigations, the Russian emperors’ attitudes towards investigative work, the commencement of F. Girs’ revision in Turkestan, its intended purpose, and its results.